The effect of climate on the production and distribution of grain crops in Babil Governorate (Journal of the College of Basic Education, 2022)
The research aims to apply the applied (deductive) approach to identify the advantages and disadvantages of this approach because of its advantages by linking theoretical studies with field studies in addition to the application of laws. The hypothesis of the research was that the variation in climatic conditions has an impact on determining the quality of agricultural production, the planting season and its quantity.